Studi Kasus Balita Usia 23 Bulan dengan Berat Badan Kurang di Desa Ulee Nyeu Puskesmas Banda Baro Tahun 2025 - Azman Bripo; Puan Nassya Amalia Islmay; Nadia AlKhalifa; Noviana Zara (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Undernutrition is a severe nutritional deficiency condition caused by inadequate daily intake of energy and protein, which occurs over a considerable period of time. Malnutrition generally affects children under five years old and is influenced by various factors. According to the National Basic Health Research Report (Riskesdas) in 2018, the national proportion of children aged 6–24 months with undernutrition and severe malnutrition was recorded at 17.7%. This study is a case report of a 23-month-old boy living in a village in 2025. The case was observed over a three-week period using a home visit approach. The diagnosis of undernutrition was established based on national guidelines, specifically the Regulation of the Indonesian Minister of Health No. 2 of 2020 concerning child anthropometric standards. Anthropometric measurements showed the child had a height of 81 cm and a weight of 8.12 kg. The child’s nutritional status was classified as underweight based on the Weight-for-Age (W/A) Z-score. Following diagnosis, the patient received nutritional education, supplementary food, appetite-stimulating vitamins, and growth monitoring. The study concluded that several determinants contributed to the underweight condition in this 23-month-old patient, including behavioral factors, incomplete immunization, and recurrent infections.